PENGGUNAAN TRICHODERMA SPP UNTUK PENGENDALIAN PENYAKIT DAN PENINGKATAN PERTUMBUHAN TANAMAN CABAI DI NAGARI TAEH BARUAH KECAMATAN PAYAKUMBUH KABUPATEN LIMAPULUH KOTA - Yulmira Yanti; Nurbailis Nurbailis; Hasmiandy Hamid; Trizelia Trizelia; Haliatur Rahma; My Syahrawati; Noveriza Hermeria (Jurnal Hilirisasi IPTEKS, 2021)
Jorong Parit Dalam Nagari Taeh Baruah, Payakumbuh District, Limapuluh Kota Regency is one of the villages that has various problems such as drought, high number of idle lands and remote access. The main crop planted during the rainy season is lowland rice, but most of the land becomes idle land during the dry season. In terms of fertilization, farmers in this location still use artificial fertilizers (chemical fertilizers) and in terms of pest and disease control they still use chemical pesticides. The solutions that can be offered are planting chili plants which are more resistant to drought, processing agricultural waste into compost as an alternative to reduce dependence on the use of chemical fertilizers, use of Trichoderma and vegetable pesticides as agents for controlling pests and diseases, and processing chili production to increase value. selling, competitiveness and community income. The purpose of this farmer group empowerment activity is to increase public knowledge about the use of Trichoderma which can increase the growth of chili plants, and can also be used as a biological agent to control pests and diseases that often attack chili plants when cultivated. The method used in this activity is socialization and counseling, structured training and direct practice in the field of Trichoderma's influence on the growth and production of chili plants. The results obtained from this activity are that the community can recognize that there are alternative controls that are more environmentally friendly than the use of synthetic pesticides. The public can also gain new understanding regarding the increased growth and yield of chili plants by utilizing the Trichoderma biological agent. So that in the end it can reduce dependence on synthetic pesticides obtained from outside. Therefore, the environment and the balance of the ecosystem in the Nagari Taeh Baruh area are maintained. The conclusion of this activity is that plant growth applied using Trichoderma spp is higher than plants that are not treated with Trichoderma spp (control). The use of Trichoderma spp is highly recommended because besides being easy to obtain, it also provides positive values for plant growth and is good for environmental technology around cultivated plants.